Islamic financial literacy among bankers in Kuala Lumpur / Mohamad Azmi Abdullah and Alex Anderson - Alex, Anderson (Faculty of Business and Management, 2015)
This article presents the findings on the study that determines the factors which influence financial literacy of bankers around Kuala Lumpur in term of Islamic financial products. The Governor of Central Bank of Malaysia pointed out several years ago that in order to make Islamic financial products acceptable to a wider spectrum of investors and businesspeople alike, financial literacy on Islamic financial products need to be enhanced. This is to facilitate transactions, with a clear understanding and appreciation of the unique characteristics and features of Islamic Finance and its real economic value. However, to date there is scarcity in the studies of Islamic financial literacy in Malaysia. This is proven when Kayed (2008) queries if there are any attempts by the research community to assess levels of Islamic financial literacy in various Muslim communities. In addition, Ahmad (2010) also points out the importance of Islamic financial literacy. These issues have actually motivated the current study to review available literatures on financial literacy mainly focusing on the Islamic financial literacy. The objectives of this study are (i) determine if the bankers possess adequate financial literacy to undertake financial decision with respect to Islamic financial products and services, and (ii) identify the significant factors that influence Islamic financial literacy among bankers. Factor analysis is used in order to identify those factors that indicate banker’s Islamic financial literacy. The findings reveal that nine factors determine banker’s financial literacy on Islamic financial products and services.